MEMBER SATISFACTION AMONG MULTIPURPOSE COOPERATIVES: ITS EFFECT ON THE INFLUENCE OF ECONOMIC FACTORS ON COOPERATIVE MEMBER COMMITMENT - Gil-Salapi, Candy Elizabeth (President University, 2024)
Cooperatives are a type of business organization that is owned and controlled democratically by its members. One of the key principles of cooperatives is to prioritize the social and economic well-being of their members and the communities in which they operate. Multipurpose cooperatives in the Philippines are cooperatives that provide a wide range of services to their members, such as credit, savings, insurance, and other services. These also perform the functions of financing and marketing. Moreover, they serve as the savings structure and source of household and agricultural supplies of its members whose capital contribution is the source of the resources of cooperatives in the savings, loans, and marketing sector along with the profit from their credit, marketing, and other economic activities (Perilla et al., 2009). As cooperatives promote economic development and poverty reduction, it is vital that these organizations sustain their operations in order that they will be able to continue these vital roles. One important means by which cooperatives will succeed is for them to develop and nurture commitment among their members (Fulton, 1999). In his study on cooperatives and member commitment in 1999, Fulton defined cooperative member commitment as